The physiological and performance development of two multiple Olympic champion rowers: a 20-year follow-up study - Mikulic, P.; Gulin, J. (Medicine & Science in Sports & Exercise, 2024)
Purpose This study reports the results of a 20-yr (2005 to 2024) follow-up study of two 2-time Olympic and 6-time world champion rowing athletes. To provide a comprehensive picture of adaptations in physiological and performance characteristics to long-term training, we monitored the athletes` physiological and performance data annually through five 4-yr developmental phases.